Optimizing the management of dry eye in corneal and conjunctival cicatrization secondary to severe burns to the eye (Ukrainian Journal of Ophthalmology, 2025)
Background: Investigation of the pathogenesis of dry eye disease (DED) in corneal and conjunctival cicatrization secondary to severe burns to the eye as well as optimization of the management of this condition is an important and relevant task of clinical ophthalmology.Purpose: To optimize the management of DED in corneal and conjunctival cicatrization secondary to severe burns to the eye on the basis of tear production studies.Material and Methods: Forty patients (60 eyes) with DED and corneal and conjunctival cicatrization secondary to severe burns to the eye and showing various reductions in Schirmer test 1 scores were included in the study. Tear substitutes (Tear Naturale; Alcon, Fort Worth, TX) or Vidisic® gel (Mann Pharma, Berlin, Germany) were administered four times a day for eyes with mild or moderate dry eye, and six times a day for eyes with severe dry eye, and tear production was assessed at 2 weeks and at 3 months.Results: At two weeks, among the eyes treated with Vidisic gel, Schirmer test score improved from 12 mm to 13 mm (p > 0.05) for eyes with mild dry eye, from 6.5 mm to 8.4 mm for eyes with moderate dry eye, and from 3.1 mm to 6.3 mm for eyes with severe dry eye. In addition, among the eyes treated with teas substitutes, Schirmer test score improved from 11 mm to 13 mm for eyes with mild dry eye, from 6.1 mm to 8.1 mm for eyes with moderate dry eye, and from 2.6 mm to 4.4 mm for eyes with severe dry eye (p < 0.05). At three months, patients who were taking their medication as per schedule had approximately the same scores as at two weeks, whereas those who discontinued taking their medication or were taking it irregularly had approximately the same scores as at baseline.Conclusion: Our findings highlight the necessity of continuous tear substitute treatment for patients with DED and corneal and conjunctival cicatrization secondary to severe burns to the eye.
Keywords: burns to the eye; dry eye disease; tear production